SWOT Analysis and Quantitative Strategic Planning Matrix (QSPM): a Strategy for Increasing School Competitiveness - Taufani Chusnul Kurniatun; Luthfi Audia Pribadi; Li Kun Mei (Universitas Negeri Malang, 2025)
The competitiveness of private schools can be seen from the school's accreditation ranking. Private schools that have low accreditation scores require strategies to increase their competitiveness. The aim of this study is to analyze the strategic position of private schools in Cirebon using SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). Data collection was carried out through observation, interviews, literature and document studies, and distributing questionnaires. Data analysis using IFAS and EFAS, SWOT analysis to analyze internal and external factors, Strengths, Weaknesses, Opportunities and Threats to obtain a strategic position. The results of the SWOT analysis show that the school being analyzed is in the Progressive Quadrant I (opportunities, strengths). The progressive quadrant in SWOT is the quadrant that shows a favorable situation for an organization. This quadrant is characterized by strengths and opportunities. In this case the school has a competitive advantage that can be utilized to seize existing opportunities. Organizations can leverage their strengths to develop new products or services, expand markets, or increase market share. Further, the strategy's priority is identified through QSPM.